Skin temperature as a thermal controller of exercise intensity - Schlader, Z. J.; Simmons, S. E.; Stannard, S. R.; Mündel, T. (European Journal of Applied Physiology, 2011)
This study examined the role of skin temperature on self-selected exercise intensity (i.e., power output). Eight well-trained, male cyclists completed two 60 min self-paced cycling bouts during which they completed as much work as possible. Using a liquid-perfused suit, skin temperature (T Sk) was changed during the two trials such that T Sk either started hot and was cooled (H to C) or started cold and was heated (C to H) throughout exercise. Pre-exercise core temperatures (T C) and heart rates (HR) were similar between trials, while T Sk, thermal comfort and thermal sensation were higher in H to C. The change in T Sk was similar in magnitude during the two trials. Work completed was greatest in C to H, which was attributed to a higher initial power output. T C was similar between trials. HR was similar until 35 min had elapsed, after which it became lower in H to C. The perception of effort increased similarly between the two trials, while thermal comfort and thermal sensation generally reflected the changes observed in T Sk. These results indicate that upon exercise commencement T Sk and the accompanying thermal perceptions are important inputs in the initial selection of exercise intensity.